Localization of acidic phospholipid cardiolipin and DnaA in mycobacteria - Maloney, Erin (2011)
Acidic phospholipids such as cardiolipin (CL) have been shown to modulate Mycobacterium tuberculosis (Mtb) DnaA interactions with ATP. In the present study, using nonyl acridine orange fluorescent dye we localized CL-enriched regions to midcell septa and poles of actively dividing cells. We also found that CL-enriched regions were not visualized in cells defective for septa formation as a consequence of altered FtsZ levels. Using Mtb cultures synchronized for DNA replication we show that CL localization could be used as a marker for cell division and cell cycle progression. Finally, we show that the localization pattern of the DnaA-green fluorescent fusion protein is similar to CL. Our results suggest that DnaA colocalizes with CL during cell cycle progression.